2008
DOI: 10.1103/physrevb.77.073303
|View full text |Cite
|
Sign up to set email alerts
|

Size dependence of the wavefunction of self-assembled InAs quantum dots from time-resolved optical measurements

Abstract: Document VersionPublisher's PDF, also known as Version of record Link back to DTU Orbit Citation (APA): Johansen, J., Stobbe, S., Nikolaev, I. S., Lund-Hansen, T., Kristensen, P. T., Hvam, J. M., ... Lodahl, P. (2008). Size dependence of the wavefunction of self-assembled InAs quantum dots from time-resolved optical measurements. Physical Review B Condensed Matter, 77(7), 073303.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
155
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 132 publications
(166 citation statements)
references
References 25 publications
10
155
0
1
Order By: Relevance
“…Our measurements are performed on an ensemble of quantum dots that are randomly oriented with respect to the interface. This situation differs from self-assembled dots that are strongly oriented [18]. A decay measurement f (t)…”
Section: B Model Of Decay Ratesmentioning
confidence: 99%
See 2 more Smart Citations
“…Our measurements are performed on an ensemble of quantum dots that are randomly oriented with respect to the interface. This situation differs from self-assembled dots that are strongly oriented [18]. A decay measurement f (t)…”
Section: B Model Of Decay Ratesmentioning
confidence: 99%
“…Recently it has been found that the emission oscillator strength can also be determined with this technique [18]. Here, we place CdSe quantum dots on different distances near a silver interface to quantitatively determine the oscillator strength as a function of emission energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the effect of variations in the LDOS will be less pronounced in the mean decay time than in the purely radiative decay time since the former also includes contributions from nonradiative decay, which is unaffected by the LDOS. 12 The experimental variations in the mean decay times are thus expected to be a conservative estimate of the actual LDOS variations in the PCM.…”
Section: Decay Dynamics Of Quantum Dots Influenced By the Local Densimentioning
confidence: 99%
“…Semiconductor quantum dots are very promising solid-state single-photon sources 3,4 thanks to their quantized energy levels, high optical quantum efficiency, 5 and coherent emission properties. 6 The harvesting of the emitted photons into a single mode is typically achieved by placing the emitters within a photonic nanostructure, such as a resonant cavity 7 or a broadband light collector like a PhC waveguide 8 or a nanowire.…”
mentioning
confidence: 99%